WOMEN ENTREPRENEURS: CHARACTERISTIC TENDENCIES ON MANAGERIAL SKILLS WITHIN DEVELOPMENT OF SMALL-MEDIUM ENTERPRISE IN MALACCA STATE, MALAYSIA - Mulyaningrum, Mulyaningrum; Aris, Amir (TRIKONOMIKA, 2019)
A recent survey conducted in several countries shows that female-owned companies involved in the global market have substantial income. Will be more optimistic if their business prospects are balanced with adequate managerial skills, and focus more on business expansion rather than just thinking about domestic-oriented female-owned companies. International trade has encouraged the growth of women’s businesses in many countries, due to an increase in managerial capacity. The global impact of women entrepreneurs is just beginning to get its intensity. The number of female business owners continues to increase steadily. The purpose of this study was to identify the characteristic tendencies in managerial skills of women entrepreneurs in Negeri Melaka. This illustrates the quality of women business owners as the key to their success in increasing the ability to develop with a more intense focus.